Strengthening the Surveillance of Antimicrobial Resistance in India Using Integrative Technologies - Kaur, Jasleen; Kaur, Jasmine; Dhama, Ajay Singh; Jindal, Shelja; Walia, Kamini; Singh, Harpreet (Frontiers in Public Health, 2022)
Background: The antimicrobial resistance (AMR) situation in India is alarming. In the absence of newer antibiotics, the best possible approach is to efficiently use the existing antimicrobials through surveillance of resistance. The data generated by AMR surveillance across the country has immense potential to drive policy decisions. However, this data is available in a variety of sources. It is imperative to have tools to integrate the data generated across the country into a single data repository. Methods An ensemble of tools (i-AMRSS, i-DIA, and i-AMRIT) have been designed and developed by the data management team at the Indian Council of Medical Research (ICMR) to strengthen surveillance of antimicrobial resistance in India. Results The i-AMRSS is a web-based ICMR's AMR surveillance system, collecting data from tertiary care centers across the country and sending it to the one-stop data repository. The i-DIA is a web-based API that simplifies the AMR data interoperability by seamlessly importing most of the LIS / HIS data from CSV files into a central, one-stop data repository. The i-AMRIT is a standalone ICMR's AMR surveillance system using integrative technologies, collecting data from all the labs across the country and sending the lab-specific cumulative data to the one-stop data repository. Discussion The tools are being used in ICMR's AMR Network and have collected over 0.4 million patient records to date. The complete system is presently being used to capture human susceptibility testing data and can be extended for capturing data using the ‘One Health' approach. The authors plan to make the system compliant with FHIR standards to enable interoperability with other countries.